2022
DOI: 10.3390/vetsci9020073
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in UT-B Urea Transporter Abundance in Fallow Deer Rumen

Abstract: Rumen studies have focused almost exclusively on livestock species under strictly regimented diets. This means that the ruminal condition of free-living and free-feeding wildlife remains practically unstudied. Urea nitrogen salvaging, a process by which urea is passed into the rumen, to both provide a valuable source of nitrogen for bacterial growth and to buffer the potentially harmful acidic effects of bacterial short chain fatty acids, has remained unexplored in wild ruminants, such as deer. UT-B2 transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Next, immunolocalization studies confirmed that both MCT1 and UT-B2 transporter proteins were predominantly located in stratum basale, in agreement with our previous studies (Zhong et al, 2022c). For MCT1, our staining confirmed MCT1 protein was found in the stratum basale of all the male adult deer rumen, except M3.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Next, immunolocalization studies confirmed that both MCT1 and UT-B2 transporter proteins were predominantly located in stratum basale, in agreement with our previous studies (Zhong et al, 2022c). For MCT1, our staining confirmed MCT1 protein was found in the stratum basale of all the male adult deer rumen, except M3.…”
Section: Discussionsupporting
confidence: 92%
“…Our recent investigations of the epithelial transporters with the rumen of a wild population of fallow deer, living in Phoenix Park in Dublin, have added new insight into the processes regulating these ruminal UT-B2 transporters. We have found that levels of the 50 kDa UT-B2 protein were significantly greater in the rumen of female adults compared to male adults that had recently been through the rutting season (Zhong et al, 2022c). Since these males had minimal food intake during that time (Apollonio & Di Vittorio 2004), these findings were interpreted as further evidence that UT-B2 abundance was highly regulated by its' role in SCFA buffering rather than just nitrogen requirements per se -as had been already reported in cows (Simmons et al, 2009) and goats (Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…This difference suggests that our UTBc19 antibodies (i) may not detect rat UT-B protein as effectively as other species (e.g human), and (ii) are more effective for Western blotting rather than immunolocalization analysis. Indeed, this second observation has also been reported in a recent study on deer rumen samples using the UTBc19 antibodies [ 30 ]. Additionally, it should also be noted that all the animals investigated in this current study were male.…”
Section: Discussionsupporting
confidence: 76%